Software radio issues in cellular base stations. - Zangi, K.C (IEEE Journal on selected areas in communications)
The use of the ?software radio? concept in cellular applications is a topic of widespread interest. Two key issues in the implementation of software radios are the development of optimal receivers that require the minimum number of bits in the wide-band analog-to-digital converter (ADC) and efficient channelizers that extract individual channels from the digitized wide-band signal. In this paper, both of these issues are studied in detail for cellular base stations. A computationally efficient wide-band channelizer is presented. This channelizer is closely related to the discrete Fourier transform filter bank used in transmultiplexers. It is shown that the complexity of the proposed channelizer is significantly less (2-50×) than the complexity of conventional channelizers. An optimal receiver that explicitly takes into account the effect of the quantization noise of the wide-band ADC is also derived. The analysis of the ADC noise provides guidelines for specifying wide-band ADC for use in cellular applications. The development of the channelizer and the optimal receiver yield important insights into the implementation of cellular software radios. All of the key results of this paper are applied to a detailed example based on the Digital Advanced Mobile Phone System (D-AMPS, IS-54/IS-136) cellular standard. The bit-error rate (BER) performance simulations of a D-AMPS wide band receiver is presented as a part of this example